Explanation of the discursive ethos of Lenín Moreno and Rafael Correa in 2018 - Andino Veloz, Byron Pacífico (2021)
This article studies the speech analysis of Rafael Correa and Lenín Moreno in a new context of Ecuador with a variation of political articulations, in which discursive strategies have a renewed formation of us and others. The objective is to investigate the construction of the discursive ethos of both politicians in 2018, through what they have said about themselves. It is a qualitative analysis of a corpus of 16 television speeches (of different types) by Moreno and 9 by Correa. The results show a strong possession of personal and political values of Moreno to support his proposal for dialogue and be a refounder of the country’s institutionality, while Correa emphasizes his moral integrity, he declares himself persecuted and as a redeemer of the country. The study makes visible how these discursive strategies built their image about the facts of the past and the present to form it differentially before their constructed opponents.